AI TECHNOLOGIES: BENEFITS CHALLENGES AND ETHCAL CONSIDIRATION - Munisa Nazirova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Artificial Intelligence (AI) is a rapidly evolving field aiming to create machines with human-like intelligence. This overview covers key AI technologies such as machine learning, natural language processing, computer vision, speech recognition, and robotics, exploring their applications in healthcare, education, entertainment, business, and security. The text delves into the benefits and challenges of AI technologies, highlighting their ethical and social implications.